2004
DOI: 10.1097/00005537-200405000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Sinusitis in Adults Must Lead to Looking for Cystic Fibrosis and Primary Ciliary Dyskinesia

Abstract: ACS should be considered a remarkable entity in which congenital abnormalities of epithelial cells are frequently detected (55% of patients). The higher frequency of mutations in ACS patients compared with the general population suggests that heterozygoty for CFTR gene mutation could be a sinusitis-causing status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Primary ciliary dyskinesia (PCD) is associated with RS as 1 of the elements of disease presentation. 610,611 Although genetic syndromes with CRS implicate genes logically linked with disease such as epithelial function 612 and defects in innate and adaptive immunity, 7 this is not always the case. Numerous genetic associations have been suggested that are difficult to link mechanistically to CRS development.…”
Section: Discussionmentioning
confidence: 99%
“…Primary ciliary dyskinesia (PCD) is associated with RS as 1 of the elements of disease presentation. 610,611 Although genetic syndromes with CRS implicate genes logically linked with disease such as epithelial function 612 and defects in innate and adaptive immunity, 7 this is not always the case. Numerous genetic associations have been suggested that are difficult to link mechanistically to CRS development.…”
Section: Discussionmentioning
confidence: 99%
“…These are clinical entities associated with CFTR dysfunction but where the diagnosis of CF cannot be unambiguously established; 1 for example, congenital bilateral absence of vas deferens (CBAVD) 9 -13 disseminated bronchiectasis, 14,15 chronic pancreatitis, 16,17 or chronic rhinosinusitis. 18,19 CFTR gene analyses are performed in specialist clinical molecular genetics laboratories closely associated with clinical genetic services or research facilities, and also in private laboratories; lists of European laboratories offering CFTR genetic testing are available at www.orpha.net or at www.eurogentest.org/web/qa/basic.xhtml. A good knowledge of CFTR diseases and their molecular pathology is required when choosing tools and strategies and when interpreting results.…”
Section: Introductionmentioning
confidence: 99%
“…Coste et al found a high prevalence of at least one CFTR mutation (38%) among patients with atypical CRS. They concluded that CFTR mutations predispose to CRS among children and adults and that mutation in the CFTR gene may play a role in the pathogenesis of CRS, in the absence of a frank CF [21].…”
Section: Discussionmentioning
confidence: 99%